(untitled) (Texas Journal of Agriculture and Biological Sciences, 2023)
The study used the type of medicinal clover (C. officinalis) as an object. The main task of the study is to create a reserve of raw materials and to determine its economic efficiency by establishing industrial plantations in the soil of the Khmer Rouge. Based on the results of the research, the foundation of the pharmaceutical industry is developed by establishing plantations in large areas of C. officinalis, which is selected separately in the soil conditions of Khmer Rouge.